2020
DOI: 10.1111/iar.12378
|View full text |Cite
|
Sign up to set email alerts
|

Teshima pyroclastics: Onset of characteristic Setouchi magmatism induced by slab melting at 14.8 Ma

Abstract: Ar-Ar ages, and petrographical and geochemical characteristics of pyroclastics and an overlying lava from Teshima Island, southwest Japan are presented. Although previous geological and age data suggested Teshima pyroclastics were products of magmatism > 3 my prior to lava flows of Setouchi volcanic rocks generated in association with southward migration of the southwest Japan arc sliver during opening of the Sea of Japan backarc basin at 15 Ma, the present results led to the conclusion that a sequence of Seto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Adakite and ADR (arc andesite, dacite, and rhyolite) fields are after Castillo (2012) fault activity. Two candidates for the origin of this andesitic magmatism can be presumed, as previously proposed for the "14 Ma" granitic magmatism of the Koshikijima Islands: (i) rift-related igneous activity associated with the opening of the Japan Sea and (ii) the extension into this area of igneous activity caused by the hot subduction of the Shikoku Basin lithosphere (which produced the Setouchi Volcanic Rocks at 15-13 Ma; Nakaoka et al, 2021;Shinjoe & Orihashi, 2017;Tatsumi, 2006;Tatsumi et al, 2010), as inferred for the 14 Ma HMA reported from the nearby Amakusa Islands (Nagao et al, 1992). The intrusion of andesite-dominant northwestsoutheast-trending dikes coeval with F1 faulting may conform to riftrelated magmatism.…”
Section: Origin Of the Granitic Magma Of The Koshikijima Islandsmentioning
confidence: 74%
“…Adakite and ADR (arc andesite, dacite, and rhyolite) fields are after Castillo (2012) fault activity. Two candidates for the origin of this andesitic magmatism can be presumed, as previously proposed for the "14 Ma" granitic magmatism of the Koshikijima Islands: (i) rift-related igneous activity associated with the opening of the Japan Sea and (ii) the extension into this area of igneous activity caused by the hot subduction of the Shikoku Basin lithosphere (which produced the Setouchi Volcanic Rocks at 15-13 Ma; Nakaoka et al, 2021;Shinjoe & Orihashi, 2017;Tatsumi, 2006;Tatsumi et al, 2010), as inferred for the 14 Ma HMA reported from the nearby Amakusa Islands (Nagao et al, 1992). The intrusion of andesite-dominant northwestsoutheast-trending dikes coeval with F1 faulting may conform to riftrelated magmatism.…”
Section: Origin Of the Granitic Magma Of The Koshikijima Islandsmentioning
confidence: 74%
“…Based on the geochronological data and the timescale of the Japan Sea opening during the late Oligocene to late Miocene (27-6 Ma), magmatic events in southwest Japan can be divided into the four episodes in chronological order: the pre-back-arc opening (>27 Ma), the early to middle stage of the back-arc opening (27-15 Ma; Figure 9), the last stage of the back-arc opening (17-12 Ma; Figure 9), and the post-back-arc opening (<10 Ma; Figure 9). The magmatic activity during the last stage of the back-arc opening was extensive and voluminous, and extended to the island-arc side of southwest Japan (Figure 1a), as represented by the high-Mg andesite of Setouchi (14.8-12.7 Ma after Tatsumi, 2006;Nakaoka et al, 2021) and the acidic volcano-plutonic complexes along the Pacific coast (15.0-14.6 Ma after Tatsumi, 2006;15.6-13.5 Ma after Shinjoe et al, 2021).…”
Section: Magmatic Activities During the Middle Miocene On The Back-arc Sidementioning
confidence: 99%
“…This activity is thought to have been induced by the upwelling of mantle diapirs and the accompanying opening of the Japan Sea Basin (Uto et al, 2004). Geochronological data indicate that magmatism on the volcanic-arc side occurred mainly in the period 16-12 Ma (Nakaoka et al, 2021;Tatsumi, 2006;Tatsumi et al, 2001), whereas the magmatism on the back-arc side occurred mainly in the period 18-12 Ma (e.g., Kimura et al, 2005;Yamamoto, 2010). The high frequency of available age data from either side of southwest Japan indicates a climax at $15 Ma.…”
mentioning
confidence: 99%